Comparison of Short-term Biodex Results After Anatomic Anterior Cruciate Ligament Reconstruction Among 3 Autografts. Issue 5 (31st May 2019) - Hughes, Jonathan D.; Burnham, Jeremy M.; Hirsh, Angela; Musahl, Volker; Fu, Freddie H.; Irrgang, James J.; Lynch, Andrew D.
Background: An individualized approach to anterior cruciate ligament reconstruction (ACLR) typically includes criteria-based postoperative rehabilitation. However, recent literature has suggested residual quadriceps weakness up to 12 months after ACLR, especially with a quadriceps tendon (QT) autograft. Hypothesis: The QT would have poorer quadriceps strength symmetry at 5 to 8 months compared with the hamstring tendon (HS) and patellar tendon (BPTB), but there would be no significant difference at 9 to 15 months among all 3 groups. Study Design: Cohort study; Level of evidence, 3. Methods: Patients who underwent anatomic primary ACLR with an autograft were reviewed retrospectively. Isometric quadriceps and hamstring strength measurements were obtained clinically at 5 to 8 months and 9 to 15 months postoperatively. Return-to-running and return-to-play criteria included greater than 80% and 90% quadriceps strength symmetry, respectively. Results: A total of 73 patients with 5- to 8-month follow-up were identified, and 52 patients had 9- to 15-month data. The QT group had a significantly lower quadriceps index at 5 to 8 months (69.5 ± 17.4) compared with the BPTB (82.8 ± 14.6; P = .014) and the HS (86.0 ± 18.6; P = .001) groups. More patients with an BPTB autograft met criteria for return to running and return to play (60% and 47%, respectively) compared with the QT group (26% and 13%, respectively) at 5 to 8 months. Given the sample sizes available, we observed no significant difference in the quadriceps index and return-to-play and return-to-running criteria at 9 to 15 months among those undergoing ACLR with a QT, BPTB, or HS graft. Conclusion: Patients undergoing ACLR with a QT graft demonstrated clinically meaningful quadriceps asymmetry at 5 to 8 months and 9 to 15 months postoperatively. Additionally, fewer patients in the QT group met criteria for return to play and running at 5 to 8 months than the BPTB and HS groups. These data suggest that a longer time to return to play and specific rehabilitation protocols that emphasize quadriceps strengthening may be necessary because of residual quadriceps weakness after ACLR with a QT graft.